Regulation of Prediction Markets Under the Financial Markets Conduct Act 2013 - Farmer, Kelsey Brooke (Victoria University of Wellington Law Review, 2015)
The Financial Markets Conduct Act 2013 (FMC Act) represents the most substantial overhaul of New Zealand’s securities law in recent history. The regulation of derivatives in particular featured high on the agenda as an area in need of reform and, as a result, the FMC Act is much more clear than the Securities Act 1978 and Securities Markets Act 1988 with respect to typical derivative agreements. The focus of this article, however, is on the atypical: the use of derivatives in prediction markets. This article examines whether New Zealand-based prediction market iPredict will be regulated under the FMC Act and, if so, how it will be regulated. The conclusion reached is that iPredict can operate under the FMC Act only if the Financial Markets Authority declares that its contracts are derivatives and grants substantial exemptions from regulatory compliance. This article then makes recommendations for a more coherent approach to the regulation of prediction markets by analogy with the new prescribed intermediary service licences under the FMC Act.